ADMINISTRATIVE JUSTICE, ADMINISTRATIVE COURT PROCEEDING AND ADMINISTRATIVE PROCESS: CONCEPTUAL-CATEGORICAL DIMENSION AND RELATION - Гончарук, Степан Тихонович; Текєджанова, Крістіна Батирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to investigate the concepts of administrative justice, administrative justice and the administrative process that are present in the current legislation of Ukraine and legal science, to analyze different points of view regarding these concepts of domestic administrative scientists and to express their own point of view on these issues. Methods of research: in the process of preparation of the article such research methods as logical-conceptual, historical-legal, cognitive-semantic, comparative-analytical, etc. were used, which made it possible to analyze the existing positions in the national doctrine concerning the formation and essence of the concepts of administrative justice, administrative proceedings and the administrative process and their relationship. Results: in view of the provisions of the current legislation and existing doctrinal concepts, they have expressed their views on the definitions of the administrative process, administrative justice and administrative justice, and proved the thesis of their close organic relationship. Discussion: the positioning of their own points of view on the essence of these concepts and their relationship, which prompts the need for further scientific understanding of these legal phenomena. The European integration course of Ukraine, deepening the democratization of our society, asserting the priority of human rights and freedoms in relations with the subjects of state-power powers require the further development of the forms of judicial protection of the rights, freedoms and interests of individuals and legal entities, comprehensive growth of law enforcement and law enforcement administrative procedural form. The administrative process provides a dynamic form of life for one of the largest arrays of legal norms, which are substantive norms of administrative law and which serve as a priority legal instrument for the implementation of tasks and functions of the executive power. Along with it, administrative justice and administrative justice play an essential role today in the proper protection of the constitutional rights, freedoms and interests of citizens and other participants in legal relations from possible unlawful acts or omissions of public authorities. At the same time, both legal theory and jurisprudence in this field, to a certain extent, require appropriate scientific interpretation and further doctrinal understanding of these concepts with a view to their further development and implementation in the legislative process. Therefore, the study of these issues always remains relevant. Based on the analysis, the authors conclude that the concept of administrative justice, administrative justice and the administrative process are organically and inextricably interconnected, complementary and have a similar functional purpose. After all, it is the duty of the rule of law to fully guarantee the guarantees of the subjective rights and interests of citizens in their relations with the subjects of public authority, which necessitates the effective functioning of administrative justice in Ukraine, which would judicially protect the rights of citizens and ensure legality in the activities of public administration bodies.